ANALISIS POLITIK MINYAK DI TIMUR TENGAH - Ismah Tita Ruslin (ILMU POLITIK UNIVERSITAS ISLAM NEGERI (UIN) ALAUDDIN MAKASSAR, 2010)
Middle East is a region full of conflicts both regional and international area, one of continuously conflicts trigger is the oil factor, an available oil in the Middle East is a blessing and a disaster other side, since the discovery of oil resources, this region has always been the international spotlight, the several of political economy interests hold on there not only among region countries but also west countries involvement as foreign policy. Oil used as a tool ad a political goal for the realization of national interests.Keywords: Oil, Politics, Middle East